Establishing a multi-stakeholder value index in medicinal plants-an economic study on selected plants in Kerala and Tamilnadu States of India - M.S. Suneetha and M.G. Chandrakanth (Ecological Economics 60 (2006), 2006)
In India, medicinal plants are valued for cultural reasons, non-monetary utilitarian purposes (food and medicine), industrial demand, and as a subset of the national biodiversity wealth. National policies to regulate the access and use in medicinal plants are to be framed in line with international regulations like Intellectual property rights and the Convention on Biodiversity. This requires prioritising between the numerous species using relevant indicators that may be market or non-market based. In this study, an attempt is made to prioritise between 18 medicinal plants selected on the basis of economic importance and endemicity in the states of Kerala and Tamilnadu. The prioritisation is done through a Value Index. Data was collected (for the year 2001) through personal interviews using individual questionnaires for the different stakeholders identified as those who gain utilitarian value from medicinal plants (tribal communities, vaidyas (shamans/native healers), Ayurvedic pharmacies, non-governmental and government organizations, exporters). The value index was developed based on scores assigned for different factors influencing the value of medicinal plants related to the different stakeholders. The factors are categorized into domestic and international variables, like domestic and international market demand, non-monetary factors and impact of benefit sharing. The contingency table of the scores for different species, analysed using Simple Correspondence Analysis provided positive (for international variables) and negative (for domestic variables) weights for different variables, indicating the contrasting variables that influence the value of a medicinal plant. In order to highlight the predominant utilities of the selected medicinal plants, the value index is decomposed into market and conservation index values. Results indicated that inclusion of perceptions of different stakeholders helps to prioritise investment decisions on medicinal plants, based on whether State desires to promote species in demand in the domestic market, international market or development of novel products based on use of medicinal plant species in indigenous communities. In addition, including benefit-sharing mechanisms into the frame of reference for the selected plants also highlights the utility of benefit sharing in sustaining indigenous traditions (by increasing value perception) through economic options.